The effect of Na+ and H2O on structural and mechanical properties of coal gangue-based geopolymer: Molecular dynamics simulation and experimental study. (25th January 2021) - Wang, Rui; Wang, Jingsong; Song, Qingchun
Highlights: Coal gangue was used to prepare geopolymer, which decrease solid waste pollution. Na2 Si2 O5 glass was selected as the original model of geopolymer for the first time. The combination of experiment and molecular dynamics simulation verified the accuracy of geopolymer molecular structure. Molecular dynamics simulation was performed to investigate the structural and mechanical properties of coal gangue-based geopolymer with different Na/Al and H2 O/Al. Abstract: The aim of this work is to study the impacts of Na + and H2 O on structural and mechanical properties of coal gangue-based geopolymer by experiment and molecular dynamics. Geopolymers were prepared by coal gangue and mixed solution of NaOH and water glass. Then X-ray fluorescence (XRF) and X-ray diffraction (XRD) were utilized to characterize the main chemical composition and crystalline phase of geopolymer after 28d curing. Moreover, Na2 Si2 O5 glass was firstly proposed to establish the molecular structure of geopolymers with different Na/Al and H2 O/Al. Structural optimization and molecular dynamics simulation were implemented under the specific force field. Simulated XRD pattern, energy and temperature curves, radial distribution function (RDF), hydrogen bond, bond angle distribution, mean square displacement (MSD) and elastic modulus of geopolymer were calculated and analyzed. Results indicated that with the increase of Na + and H2 O content, structure of geopolymer became more stable and mechanical properties were improved significantly.